PENGARUH NILAI TUKAR TERHADAP HARGA SAHAM SETELAH INITIAL PUBLIC OFFERING (IPO) - Andriana, Denny (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to examine the effect of exchange rate on stock prices after Initial Public Offering (IPO) on companies listed on the Indonesia Stock Exchange. Observations made on 137 companies that conduct an IPO in the period of 2009 to 2014. The purposive sampling method undertaken in this study resulted in 78 companies that became the research sample. Data analysis technique used in this research is simple regression model. The test results prove that exchange rate has positive but not significant effect on stock price after IPO. The value of determination coefficient is 0.047 (4.7%) indicating that the exchange rate variation can only explain 4.7% against stock price variation after IPO. The other 95.3% is another variable not included in this study.